Peran Profitabilitas Dalam Memoderasi Dampak Corporate Governance Terhadap Integritasi Laporan Keuangan - Gusmi Arni; Purwanti (LPPM STIE PPI, 2025)
Introduction/Main Objectives: This study aims to explore the relationship that can affect the integrity of financial statements with institutional ownership and independent commissioners. Background Problems: The condition of stock market prices declined in 2020 and then changed fluctuatingly, tending to decrease until the following years. Novelty: The existence of profitability variables as a moderating relationship in the study. Research Method: The research method used is a quantitative approach using secondary data through a purposive sampling method as a sampling method. Findings/Results: Institutional ownership has a significant negative effect on the integrity of financial statements, then independent commissioners have a significant positive effect on the integrity of financial statements, and profitability is able to strengthen the relationship to the integrity of financial statements. Conclusion: This finding indicates that an increase in the amount of institutional ownership will potentially lead to non-transparent and manipulative practices or behavior that are detrimental to the integrity of financial statements.